If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 6x + 2 Reorder the terms: 5 + 5x = 6x + 2 Reorder the terms: 5 + 5x = 2 + 6x Solving 5 + 5x = 2 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5 + 5x + -6x = 2 + 6x + -6x Combine like terms: 5x + -6x = -1x 5 + -1x = 2 + 6x + -6x Combine like terms: 6x + -6x = 0 5 + -1x = 2 + 0 5 + -1x = 2 Add '-5' to each side of the equation. 5 + -5 + -1x = 2 + -5 Combine like terms: 5 + -5 = 0 0 + -1x = 2 + -5 -1x = 2 + -5 Combine like terms: 2 + -5 = -3 -1x = -3 Divide each side by '-1'. x = 3 Simplifying x = 3
| (c+3)(c+4)=2 | | 7x+3=-2x+21 | | Mp+mz=r | | lnx^7-10lnx=1 | | 3+2*[(2+1)*5+8]= | | -5x+2=-2x-31 | | 2y+6+8y+10+y+32=180 | | X^2+13x-64=0 | | 5m-28=-33+6m | | 3x^2+56=-136 | | 9n-23=17+n | | 2y^2-4y-8=y^2+y | | (1.8X+0)-(1.4X+0.6)= | | 2(x+4)-126=0 | | 3+y=10+3 | | m^2+m+.25=0 | | p+12=24 | | (5-4x)(x-5)=0 | | 12x^2-52x+48=0 | | ln(11x-7)=0 | | 3y-8y=12 | | 6x+5=54-x | | 0.2x+0.01=0.2y | | 20%-39.99= | | 7-9x+10+5x+5x-3=9+2*4 | | 2x-3=1.4 | | -4x*x-4x= | | 1/7(r-49)=6/7 | | 15x^5-21x^4-18x^3=0 | | -12y+7=-13y+1 | | 32/8-23/4= | | 2x+6+3x=x+4x+4.5 |